Methodology for images grabbing of massive numbers of moving fruits - YING Yi-bin; RAO Xiu-qin; HUANG Yong-lin (浙江大学学报. 农业与生命科学版)
The real-time image acquisition system of massive numbers of moving fruit is one of the key sub-systems of quality inspection and grading robot of fruits, which consisted of a computer, a Panasonic CP410 color camera, a Meteor Standard/ Ⅱ grabber, eddy proximity sensors and a set of real-time image acquisition software. The proximity sensors were used to track the fast moving and rotating fruits on the conveyers and then trigger the camera and the grabber to acquire image of moving fruits, and the software was programmed with Microsoft Visual C++6.0 and MIL-LITE function library. In the light of the characteristics and requirement of real-time inspection and grading, the continuous area-scans approach was put forward to acquire the image of fruits from time t1 to time tn　in a time-series manner. These progressive time-series digital images were synthesized in system memory so that the overall composite sides of the fruits could be examined. This new approach enables the large coverage of multiple fruits simultaneously and utilizes less equipment for an entire machine. The test results verified that this system could grab 12 frames per second with the triggering from the proximity sensors.